1995
DOI: 10.1002/j.1460-2075.1995.tb07228.x
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of SYT to two genes, SSX1 and SSX2, encoding proteins with homology to the Kruppel-associated box in human synovial sarcoma.

Abstract: We demonstrate that the cytogenetically defined translocation t(X;18)(p11.2;q11.2) found in human synovial sarcoma results in the fusion of the chromosome 18 SYT gene to either of two distinct genes, SSX1 or SSX2, at Xp11.2. The SSX1 and SSX2 genes encode closely related proteins (81% identity) of 188 amino acids that are rich in charged amino acids. The N‐terminal portion of each SSX protein exhibits homology to the Kruppel‐associated box (KRAB), a transcriptional repressor domain previously found only in Kru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
343
0
5

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 434 publications
(372 citation statements)
references
References 36 publications
19
343
0
5
Order By: Relevance
“…Fusion of SYT to SSX1, SSX2 and SSX4 causes inappropriate transcription of SSX sequences in synovial sarcoma that is characteristic of this tumour group (Crew et al, 1995;Skytting et al, 1999). Although SSX1 and SSX2 were not present on the microarray, they contain significant regions that exactly match SSX4 sequences and their transcripts would be likely to crossreact with SSX4 in these microarray studies.…”
Section: Gene Clustering Analysismentioning
confidence: 93%
See 1 more Smart Citation
“…Fusion of SYT to SSX1, SSX2 and SSX4 causes inappropriate transcription of SSX sequences in synovial sarcoma that is characteristic of this tumour group (Crew et al, 1995;Skytting et al, 1999). Although SSX1 and SSX2 were not present on the microarray, they contain significant regions that exactly match SSX4 sequences and their transcripts would be likely to crossreact with SSX4 in these microarray studies.…”
Section: Gene Clustering Analysismentioning
confidence: 93%
“…Synovial sarcomas are relatively well defined with two clear subcategories designated monophasic and biphasic, distinguishable following immunohistochemical examination (Fisher, 1998). The majority of cases of synovial sarcoma contain a t(X;18)(p11.2;q11.2) translocation that results in the fusion of the chromosome 18 gene SYT to three closely related genes SSX1, SSX2 and SSX4 on the X chromosome (Clark et al, 1994;Crew et al, 1995;Skytting et al, 1999). However, this tumour is of uncertain histogenesis and despite its name, it does not appear to originate from the synovium.…”
mentioning
confidence: 99%
“…All SSX genes encode proteins of 188 amino acids, which are rich in charged amino acids and contain an acidic C-terminal tail. Normal SSX expression has been found in testis and, at a low level, in thyroid (Crew et al, 1995;Gure et al, 1997Gure et al, , 2002. Ectopic SSX expression has been observed in various tumor types, in particular in human melanomas (Tureci et al, 1998(Tureci et al, , 1996dos Santos et al, 2000b).…”
Section: Introductionmentioning
confidence: 99%
“…Cytogenetically, it is characterized by a recurring chromosomal translocation, t(X;18)(p11;q11), which is found in more than 95% of all cases (dos Santos et al, 2001;Ladanyi et al, 2002). As a result of this translocation, the SS18 gene (previously called SYT) on chromosome 18 is fused to either one of the three closely related SSX genes on the X chromosome, SSX1, SSX2 or SSX4 (Clark et al, 1994;Crew et al, 1995;de Leeuw et al, 1995;Skytting et al, 1999). The occurrence of either SS18-SSX1 or SS18-SSX2 fusions was found to correlate to histologic (de Leeuw et al, 1994) and/or prognostic (Kawai et al, 1998;Ladanyi et al, 2002) parameters, although the latter observation could not be confirmed (Guillou et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation